Studying Sustained Attention and Cognitive States in Remote Technical Interviews - Ford Robinson, Denae; Barik, Titus; Parnin, Chris (In proceedings of the ACM ICER 3rd International Workshop on Eye Movements in Programming (EMIP), 2015)
In this position paper, we argue that eye tracking can be used to understand the underlying cognitive states of a programmer during remote technical interviews, specifically programming interviews. We describe a mock-interview experiment that applies eye tracking to identify these cognitive states, and propose two computational interventions that support an interviewer and a candidate. We posit that these interventions will increase the effectiveness of remote technical interviews.